MAIN ASPECTS OF USE MARKETING ON THE «B2B» MARKET - Гуменюк, Алла; Гарматюк, Олена (Modern engineering and innovative technologies, 2022)
Features of the «B2B» market «dictate» their conditions of use of marketing tools. Orientation to the client, technical complexity of the product, interdependence of the buyer and the seller - all this makes the use of marketing tools specific. The articl